A New Technique for Quantitative Determination of Dexamethasone in Pharmaceutical and Biological Samples Using Kinetic Spectrophotometric Method. (8th February 2015) - Akhoundi-Khalafi, Ali Mohammad; Shishehbore, Masoud Reza
Abstract : Dexamethasone is a type of steroidal medications that is prescribed in many cases. In this study, a new reaction system using kinetic spectrophotometric method for quantitative determination of dexamethasone is proposed. The method is based on the catalytic effect of dexamethasone on the oxidation of Orange G by bromate in acidic media. The change in absorbance as a criterion of the oxidation reaction progress was followed spectrophotometrically. To obtain the maximum sensitivity, the effective reaction variables were optimized. Under optimized experimental conditions, calibration graph was linear over the range 0.2–54.0 mg L −1 . The calculated detection limit (3s b / m ) was 0.14 mg L −1 for six replicate determinations of blank signal. The interfering effect of various species was also investigated. The present method was successfully applied for the determination of dexamethasone in pharmaceutical and biological samples satisfactorily.